Food issues 食事 Interdisciplinary Studies on Food in Modern and Contemporary East Asia - Castorina, Miriam; Cucinelli, Diego (Studi e saggi, 2021)
Food issues 食事. Interdisciplinary Studies on Food in Modern and Contemporary East Asia concentrates on the relationship among food, culture, literature, and language in a comparative, transcultural, or literary perspective. The contributions investigate these aspects from different approaches: historical, sociological, anthropological, religious, linguistic, and want to deepen issues such as the symbolic value of food; food as an essential element for the construction of individual identity and a sign of belonging to a community; food as an intercultural medium; food as language and the language of food. The articles included in the volume are organized in a Japanese and a Chinese section and use different approaches within humanities disciplines to explore topics ranging from classical and contemporary East Asian literature to present-day issues, focusing on Food Culture and its declinations.